A Research Funder's Open Access Policy - Farley, Ashley (My University, 2024)
A Research Funder's Open Access Policy - AfricArXiv Open Science Webinar Series 2024 Watch the recording here: https://africarxiv.pubpub.org/pub/amicfn6b/
The Bill & Melinda Gates Foundation’s Open Access Policy The Bill & Melinda Gates Foundation is committed to information sharing and transparency. We believe that published research resulting from our funding should be promptly and broadly disseminated. We have adopted an Open Access policy that enables the unrestricted access and reuse of all peer-reviewed published research funded, in whole or in part, by the foundation, including any underlying data sets. Read about the policy here: openaccess.gatesfoundation.org/open-access-policy/ 2025 Policy Refresh Since 2015, the Bill & Melinda Gates Foundation has led a bold Open Access policy that prioritizes the access, transparency, and equity of funded research. With a decade of experience and lessons learned, the foundation is refreshing its Open Access policies to address ongoing challenges and advance systemic change in scholarly publishing. The policy refresh will take effect on January 1st, 2025. Read about the Open Access 2025 Policy here: https://openaccess.gatesfoundation.org/open-access-policy/2025-open-access-policy/
Keywords: Open Access; Open Access Policy; Research Funding; Academic Research; Scholarly Communication; Webinar; AfricArXiv; Bill and Melinda Gates Foundation